Somatic Embryo Yield and Quality From Norway Spruce Embryogenic Tissue Proliferated in Suspension Culture - Välimäki, Sakari; Hazubska-Przybył, Teresa; Ratajczak, Ewelina; Tikkinen, Mikko; Varis, Saila; Aronen, Tuija (Frontiers in Plant Science, 2021)
Somatic embryogenesis is being piloted for the commercial production of genetically improved Norway spruce (Picea abies L. Karst) forest regeneration material in Finland. The main challenge to making the process commercially relevant is the dependence on time-consuming and highly skilled manual labor. Automation and scaling up are needed to improve cost-effectiveness. Moving from the proliferation of embryogenic tissue on semisolid media to suspension cultures could improve process scalability. In a series of four experiments (overall, with 20 cell lines, 4–9 per experiment) the suitability of proliferation in suspension culture for Norway spruce somatic embryogenesis was evaluated based on growth rate, indicators of stress conditions, good-quality cotyledonary embryo yield, and embling survival in a greenhouse. The proliferation rate in suspension was found equal to on semisolid media, but with remarkable genotypic variation. Embryogenic tissue matured directly without pre-treatments from suspension onto semisolid media produced lower numbers of good-quality embryos than tissue matured from semisolid media. Rinsing the suspension-grown tissue with hormone-free liquid media before maturation improved embryo yield, bringing it closer to that of semisolid-grown tissue. Decreasing 6-benzylaminopurine and 2,4-dichlorophenoxyacetic acid concentrations in suspension proliferation media to 0.5 or 0.1 times those in semisolid media did not affect tissue growth and did not improve embryo production. H2O2 content and guaiacol peroxidase activity were elevated in suspension cultures compared to on semisolid medium, which had the same plant growth regulator content. In one experiment out of four greenhouse survival of germinants was lower when proliferation was carried out in full strength suspension than on semisolid media, in other experiments the survival rates were equal.